Remediation of Frogmore Mine Spoiled Soil with Nano Enhanced Materials. Issue 3 (3rd April 2022) - Adhikari, Tapan; Dharmarajan, Rajarathnam; Lamb, Dane; Zhang, Huiming
ABSTRACT: A large amount of waste material and tailings, generated from opencast mineral extraction, released different heavy metals and metalloids that polluted the mine surroundings soil. In the present investigation, an attempt was made to revegetate the open-cut mine affected area. Bulk soil samples were collected from derelict Frogmore tungsten mine site, and after physicochemical characterization of the soil samples, pot culture experiments were conducted in a green house. The different experimental soils like control soil, polluted soil, and polluted soil treated with the combined amendment, viz . Nano chailings (8 t/ha) + Nano composite of Zeolites + Nano Clay (Bentonite) (5%) + Nano composite of Zeolite + Zero valent iron (5%) + 5 t/ha FYM (Farm Yard Manure), were used in the investigation and maize ( Zea mays L.) was taken as a test crop. This paper focused on amendments based on nano-enhanced materials. Amongst heavy metals like Cd, Ni, Zn, Cu, Pb, etc ., Pb recorded the highest amount (125 mg/kg), which caused drastic reduction in different growth parameters of maize plant grown in mine spoiled soil. Microscopic structural changes, such as decrease in intercellular spaces, stomatal opening, shrinkage of palisade and epidermal cells, occurred in maize leaves grown in the mine polluted soil. Experimental results also revealed significant decrease in the fresh weight, dry weight, height, and girth of maize plants grown in mine spoiled soil. The contaminant distribution in the mine site should be considered in the design of management and remediation strategies. The possible practical consequences of these findings might be the application of nano-enhanced materials for the remediation and revegetation of the abandoned mine spoiled soils.